Alkoxide-catalyzed addition of alkyl carbonates across alkynes – stereoselective synthesis of (E)-β-alkoxyacrylates. Issue 3 (19th December 2016) - Wendling, Timo; Risto, Eugen; Erb, Benjamin; Gooßen, Lukas J.
Abstract : Terminal alkynes were converted to ( E )-β-alkoxyacrylates via regio- and stereoselective addition of dialky carbonates catalyzed by potassium methoxide. Abstract : Dialkyl carbonates were found to regio- and stereoselectively add to terminal alkynes in the presence of catalytic amounts of potassium methoxide. Various synthetically meaningful aryl- and heteroaryl-substituted ( E )-β-alkoxyacrylates were thus obtained in high yields and with near-ideal atom economy.